Analysis of Village and Poverty Funds in Indonesia - Indria Mayesti; Amri Amir; Surya Hidayat; Syaparuddin Syaparuddin (Budapest International Research and Critics University, 2022)
The purpose of the study through a statistical model of ratio, growth and moving average found that the use of village funds in Indonesia during the 2015-2020 period was an average of IDR 38 (trillion rupiah) with the highest growth rate of village funds in 2016 of 124.78%, the budget which is not in line with the percentage of poverty in Indonesia of 3.41% or 17,280,000 (people). The lowest growth in village funds was in 2018 at 0.16% and not in line with the decline in poverty in Indonesia at 3.42% or at 25,670,000 (people). The village fund for a month is Rp. 134,876 assuming 4 members and the ratio of village funds to poverty is Rp.539, 504 or people's income is classified as low. UThe highest village fund budget occurred in 2018 of Rp. 50 (trillion rupiah) in the same year poverty increased in Indonesia to 27,293,333 (people) or 11.13%. The results of the moving average model found a value of 3.10%, meaning that ifAssuming there is an increase in the poverty rate by 3.43%, then the village fund becomes Rp.472.595 or is in a position above the poverty line.To overcome the problem of poverty is to increase the ratio of village fund budgets to the number of poor people and implement productive empowerment programs that have implications for increasing community income and involving village community participation.